Management of Macrophomina dry root rot of Safflower with different bioagents: Management of Macrophomina dry root rot of Safflower with different bioagents - N SHRAWANI; C V AMBADKAR; M G PATIL (Journal of Oilseeds Research, 2023)
Safflower (Carthamus tinctorius Linn) is a significant oilseed crop that is grown in more than 60 nations throughout the world. M. phaseolina is a facultative parasite and causal agent of seedling blight, root rot and charcoal rot of Safflower. Considerning the harmful effects of chemical fungicides on environment, present investigation was carried out to test seven bioagents in vitro for their bio-efficacy in inhibition of the growth of M. phaseolina. In dual culture technique, highest per cent inhibition of M. phaseolina was exhibited by the bio-agent Tricoderma harzianum (88.15%) followed by Tricoderma virensand T. asperellum which inhibited mycelial growth to an extent of 84.07 and 78.89 per cent, respectively.